2014
DOI: 10.1016/j.biomaterials.2014.05.082
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of cardiac progenitor cell function by hydrogel-dependent Notch1 activation

Abstract: Myocardial infarction is the leading cause of death worldwide and phase I clinical trials utilizing cardiac progenitor cells (CPCs) have shown promising outcomes. Notch1 signaling plays a critical role in cardiac development and in the survival, cardiogenic lineage commitment, and differentiation of cardiac stem/progenitor cells. In this study, we functionalized self-assembling peptide (SAP) hydrogels with a peptide mimic of the Notch1 ligand Jagged1 (RJ) to evaluate the therapeutic benefit of CPC delivery in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 53 publications
5
53
0
Order By: Relevance
“…biological molecules, adhesion ligands, adjustable ligand densities, cytokines, and growth factors), screening of suitable biomaterials depending upon the intended application, and the precise design of natural and synthetic biomaterials may alleviate these shortcomings and enhance cell transplantation efficiency and the associated therapeutic benefits [292]. Moreover, smart biomaterials can be designed as cell vehicles that can extend the viability of transplanted cells in vivo, control the differentiation of those cells into particular lineages, and allow for the precise release of cells [34,[293][294][295].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…biological molecules, adhesion ligands, adjustable ligand densities, cytokines, and growth factors), screening of suitable biomaterials depending upon the intended application, and the precise design of natural and synthetic biomaterials may alleviate these shortcomings and enhance cell transplantation efficiency and the associated therapeutic benefits [292]. Moreover, smart biomaterials can be designed as cell vehicles that can extend the viability of transplanted cells in vivo, control the differentiation of those cells into particular lineages, and allow for the precise release of cells [34,[293][294][295].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…After being administered, cells can be nearly gone as soon as 1 to 3 days after transplantation [44,45]. However, some authors reported signs of stem cell survival up to 1 week [8,16,60,100,104], 1 month [14,18,23,27,30,37,46,52,67,105] and, most strikingly, up to 1 year [26]. When retained cells are quantified, we find that less than 3% of the stem cells survive more than 4 weeks [59,70] and that percentage drops to levels below 1% when the assessment is made 16 weeks after transplantation [106].…”
Section: Mechanistic Challengesmentioning
confidence: 99%
“…1). Surprisingly, though, they often exhibit poor survival and engraftment [57][58][59], that is why paracrine activity, mainly pro-angiogenic, has been attributed as their main mechanism of action, rather than the anticipated cardiomyogenic activity [60,61].…”
Section: Cardiac Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations